Synthesis, Electrochemical and Photochemical Properties of Sulfanyl Porphyrazine with Ferrocenyl Substituents - Mina Hassani; Amanda Leda; Weronika Porolnik; Michal Falkowski; Tomasz Rębiś; Jaroslaw Piskorz; Lukasz Popenda; Michal Wicinski; Dariusz T. Mlynarczyk; Nejat Düzgüneş; Michal P. Marszall (Molecules, 2023)
Ferrocene is useful in modern organometallic chemistry due to its versatile applications in material sciences, catalysis, medicinal chemistry, and diagnostic applications. The ferrocene moiety can potentially serve many purposes in therapeutics and diagnostics. In the course of this study, (6-bromo-1-oxohexyl)ferrocene was combined with dimercaptomaleonitrile sodium salt to yield a novel maleonitrile derivative. Subsequently, this compound was subjected to an autocyclotetramerization reaction using the Linstead conditions in order to obtain an octaferrocenyl-substituted magnesium(II) sulfanyl porphyrazine. Following that, both compounds—the maleonitrile derivative and the porphyrazine derivative—were subjected to physicochemical characterization using UV-Vis, ES-TOF, MALDI-TOF, and one-dimensional and two-dimensional NMR spectroscopy. Moreover, the sulfanyl porphyrazine was subjected to various photophysical studies, including optical absorption and emission measurements, as well as the evaluation of its photochemical properties. Values of singlet oxygen generation quantum yields were obtained in different organic solvents. The electrochemical properties of the synthesized compounds were studied using cyclic voltammetry. According to the electrochemical results, the presence of electron-withdrawing oxohexyl groups attached to ferrocene afforded significantly more positive oxidation potentials of the ferrocene-based redox process up to 0.34 V vs. Fc+/Fc.